2021
DOI: 10.3390/vaccines9101132
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Attitudes, Norms, and Efficacy on Shifting COVID-19 Vaccine Intentions: A Longitudinal Study of COVID-19 Vaccination Intentions in New Zealand

Abstract: While public intentions to get a COVID-19 vaccine have been shifting around the world, few studies track factors that help us understand and improve COVID-19 vaccine uptake. This study focuses on identifying changing public intentions to get a COVID-19 vaccine in New Zealand, a country that has been largely successful in containing the pandemic but risks new outbreaks as less than 20% of the population is fully vaccinated by August 2021. Data on COVID-19 intentions were collected just after the vaccine approva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
25
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 37 publications
(67 reference statements)
7
25
0
3
Order By: Relevance
“…In other words, while there was a shift towards the decision to take COVID-19 vaccine, a minority continued to be opposed to a vaccine. A similar pattern of changes in attitudes (or behavior) towards vaccination was also observed in other countries (e.g., [6]). It is possible that the decision to vaccinate (despite previous hesitation) was influenced by the extensive information campaign promoting vaccination that appeared in the Polish media, as well as the benefits for vaccinated persons (e.g., possibility to travel abroad without COVID-19 testing).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In other words, while there was a shift towards the decision to take COVID-19 vaccine, a minority continued to be opposed to a vaccine. A similar pattern of changes in attitudes (or behavior) towards vaccination was also observed in other countries (e.g., [6]). It is possible that the decision to vaccinate (despite previous hesitation) was influenced by the extensive information campaign promoting vaccination that appeared in the Polish media, as well as the benefits for vaccinated persons (e.g., possibility to travel abroad without COVID-19 testing).…”
Section: Discussionsupporting
confidence: 82%
“…Our study adds to the existing literature firstly because it aimed to investigate not only the intention to vaccinate against COVID-19 (right after the start of the vaccination campaign), but also the actual behavior (vaccination or not) of the same group of people six months later. Moreover, we examined not only the reasons for the decision not to vaccinate (which has been examined in many studies, e.g., [6]) but also how those who wanted to receive the vaccination (in the first measurement) or had been vaccinated (in the second measurement) justified their choice (which, to our knowledge, has been less frequently studied).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies [23][24][25] showed that acceptors had positive consequences of receiving the COVID-19 vaccine more often than non-acceptors. This includes (1) reducing the risk of COVID-19 infection, (2) being able to participate in social and cultural activities, (3) being able to reopen children's schools, (4) reducing COVID-19-related costs, (5) increased employment and income opportunities, and (6) participation in group prayers.…”
Section: Discussionmentioning
confidence: 99%
“…TPB research shows that both perceived descriptive and injunctive norms are positively related to vaccine uptake [ 63 , 68 , 69 , 70 , 71 ]. Coronavirus SARS-CoV-2 vaccination intentions correlate positively with a positive attitude toward vaccination, with perceived subjective norms in favor of vaccination among friends, family [ 69 , 72 ], doctors [ 73 , 74 ], and with high perceived behavioral control [ 11 , 27 , 63 , 68 ].…”
Section: Literature Backgroundmentioning
confidence: 99%
“…and this has directed the research of its determinants to an approach mostly by compartment ponds between the different theoretical frameworks [ 4 , 5 ]. Moreover, the intention to get vaccinated is influenced by a plethora of factors: (i) self-protection factors (on one hand, being vaccinated is an action to protect one’s health in the long term, but on the other, it is simultaneously seen as a possible health hazard) [ 6 , 7 , 8 ]; (ii) socio-relational factors [ 9 ]; (iii) political and ideological factors [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%